Sleeper straddle : a novel in stories [large type] - Rowe, Christopher; Vaughn, Carrie; Priest, Cherie; Wu, William F., 1951-; Williams, Walter Jon; Leigh, Stephen; Mohanraj, Mary Anne; Gladstone, Max (Thorndike Press large print high octane., 2024)
"In this original collection of eight interwoven short stories, an alien virus ravages the world. Those infected either die, receive superpowers, or are bizarrely mutated. Dubbed "The Sleeper," Croyd Crenson undergoes hibernations that span days, weeks, or even months. After each hibernation, he awakens with a new appearance and set of powers until his next sleep shuffles the cards anew. His latest awakening has left him split into six different incarnations. What follows is a journey through Croyd's colorful life, through the lens of some who have encountered the world's most unusual wild carder"--